Building agreements among stakeholders - Wollenberg, Eva Karoline; Anau, N.; Iwan, R.; Heist, M. van; Limberg, G.; Sudana, M. (2002)
CIFOR facilitated 27 communities in the Upper Malinau watershed to develop agreements about their village boundaries and map them through participatory methods. Decentralization reforms created new values of forest resources and uncertainties that increased conflict over local resources. The authors report on the nature of these conflicts, the stability of agreements and the factors affecting how agreements were reached.